Caracterização genotípica e fenotípica de isolados de Toxoplasma Gondii de galinhas caipiras criadas de forma extensiva no município de Uberlândia - MG - Costa, Luiz Carlos Gebrim de Paula (2016)
Toxoplasma gondii is an ubiquitary parasite of animals and humans. We report here the isolation and genotyping of a new T. gondii strains from free-range chicken in Uberlândia, Brazil. The parasite showed new atypical genotypes when compared with the clonal lineages (I, II and III). The virulence of this isolate, named TgChBrUD5 was tested using BALB/c mice in order to observe the mortality during the period of 30 days. All infected mice with 103 parasites died after 14th days post-infection. TgChBRUD5 genotyping was performed using the single nucleotide polymorphism (SNP) by use of 7 microsatellite loci and 5 gene markers (GRA6, GRA7, SAG1, PK1 and ROP18 sequences). The comparison of microsatellite sequences and SNP indicate that TgChBRUD5 are resultant of combinations of Type I, II and III strains, but more related to the type clonal I or recombinant BrI. The genomic characterization of T. gondii isolates based on SNPs constitutes a useful tool to determine the virulence degrees of the parasite population, as mirror of its epidemiology and pathogenicity.